Management of Neonatal Priapism: Report of Two Cases and Review of the Literature - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; ÇAM, HAYDAR KAMİL (GALENOS YAYINCILIK, 2016)
Priapism in a newborn is a rare entity with only 15 cases reported in the literature since 1879. The most commonly detected etiologic factor is polycythemia, but most of the cases are idiopathic. Conservative treatment seems to be sufficient and surgical approach is usually unnecessary. Here, we present a prolonged erection in two newborns which occurred at the first day of life and detumescence was achieved with conservative approach at the 6th and 7th day of life, respectively. We also reviewed the literature to investigate the most adequate evaluation and management criteria.
Keywords: Idiopathic; conservative; priapism; neonatal; management; PROLONGED PENILE ERECTION; IDIOPATHIC PRIAPISM